The myth of American religious freedom - Sehat, David (Oxford University Press, 2010)
In the battles over religion and politics in America, both liberals and conservatives often appeal to history. Liberals claim that the Founders separated church and state. But for much of American history, David Sehat writes, Protestant Christianity was intimately intertwined with the state. Yet the past was not the Christian utopia that conservatives imagine either. Instead, a Protestant moral establishment prevailed, using government power to punish free thinkers and religious dissidents. In The Myth of American Religious Freedom, Sehat provides an eye-opening history of religion in public l